IMPLEMENTASI KERJASAMA INDONESIA DENGAN AS DALAM PENANGANAN AKSI TERORISME DI INDONESIA - Rilistya, Cesarani; Susitianingsih, Hermini; Paramasatya, Satwika (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
In 2002, Indonesia was shocked by bomb explosion in Bali which causedmore than 200 casualties. Indonesian Government started to be aware withthe lethal danger of terrorism, establishing Government Regulations in Lieuof Law No. 1 Year 2002 on Combating Criminal Acts of Terrorism(Peraturan Pemerintah Pengganti Undang-undang Nomor 1 Tahun 2002tentang Pemberantasan Tindak Pidana Terorisme) and establishing Counter-Terrorism Coordinating Desk (DKPT) which is now BNPT (Badan NasionalPemberantasan Terorisme). The Bali Bombing case also received the UnitedStates’s attention and so they offered Indonesia cooperation in combatingterrorism. The cooperation between Indonesia and the United States isactualized with the implementation of counter terrorism. This research willexplain the process of the implementation of Indonesia-United Statescooperation on counter terrorism in Indonesia. On the process of thecooperation, there are supporting and inhibiting factors that affect theconsummation of Indonesia-United States cooperation on counter terrorism.This research uses qualitative method with explanative analysis. The researchshows that the cooperation between Indonesia-United States helps Indonesiapreventing terrorism acts. The prevention form on terrorism mostly done bythe Special Detachment 88 (Densus 88), which successfully combat theterrorists and raid the terrorists’s quarters. The reliable investigation andraid skills came from United States' training provided by the FBI to the bestIndonesian police forces.